Analysis of mass transport in solid oxide fuel cells using a thermodynamically consistent model. (23rd December 2021) - Ma, Jingbo; Yan, Mufu; Zhang, Yanxiang; Qin, Shaohua
Summary: Solid oxide fuel cells (SOFCs) are promising electrochemical energy conversion devices that convert fuels into electricity efficiently and cleanly. Modeling mass transport in SOFCs is essential for understanding and designing better fuel cells. In the last decades, the modeling of SOFCs has made significant progress, raising several issues to be addressed. One major issue is how to couple the electronic conduction in electrolyte and the other transport processes in a thermodynamically consistent way. Herein, we developed an analytical model to address this issue. The model is verified by the literature data and can predict the low open‐circuit voltage that most present models do not describe. By combining Fick's law for gas transport and the Butter‐Volmer equation for electrode reactions, the ionic and electronic current through the cell, the overpotentials (oxygen partial pressures) across electrode/electrolyte interfaces, and voltage‐current performance of SOFCs can be calculated and are validated by experimental data of SOFCs with ceria‐based electrolyte. The influence of the anode support parameters, including porosity, tortuosity, pore diameter, and support thickness, is studied, guiding SOFCs' microstructure design. The model can also serve as a sub‐model for stack‐ and system‐scale design of SOFCs. Abstract : In the article "Analysis of mass transport in solid oxide fuel cells using a thermodynamically consistent model.", we developed an analytical model to couple the electronic conduction in electrolyte and the other transport processes in a thermodynamically consistent way. The model could successfully simulate the voltage‐current performance of the SOFCs. The transport process in the anode is analyzed using this model. As the author of this article, we (Jingbo Ma, Mufu Yan*, Yanxiang Zhang* and Shaohua Qin * ), state the novelty of this work here.